How can artificial intelligence-powered chatbots help policymakers? A roadmap for Kenya - Akuku, Boniface; Breisinger, Clemens; Karugia, Joseph; Koo, Jawoo; Keenan, Michael; Ndegwa, Richard (CGIAR System Organization, 2023)
Policymakers are under tremendous pressure to address multiple challenges facing food systems amid widespread budgetary constraints. Having a good evidence base to inform policy and investment decisions is more important than ever, and the rise of large language models (LLMs) raises the question of if and how artificial intelligence can help policymakers analyze evidence information and use them to draft policies effectively. With Kenya’s Ministry of Agriculture and Livestock Development (MoALD) declaring a new era integrating science into policymaking, now is an opportune moment to explore what this question could mean for Kenya.